THE INFLUENCE OF INSTRUCTIONAL LEADERSHIP, ACHIEVEMENT MOTIVATION, AND QUALITY OF WORK LIFE ON TEACHER JOB SATISFACTION AT AL WASHLIYAH PETUMBUKAN VOCATIONAL SCHOOL, PETUMBUKAN, DELI SERDANG - Kayamuddin Saragih (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: The purpose of this study is the influence of instructional leadership, achievement motivation and quality of work life on teacher job satisfaction at Al-Washliyah vocational high school, Galang District, Deli Serdang Regency, North Sumatra Province. The method used in this study, Quantitative Method with the teacher population as the object in Vocational High Schools there are 68 people, the sample used is the entire number of teachers. The research instrument using a questionnaire has been tested for its validation and reliability. The results of this study are shown by the coefficient of determination (R square) = 74.0% and the remaining 26% is determined by other factors. The results of simple regression analysis show the regression equation Ŷ = 8.638+ 0.838 X1, which means that the increase is 0.838. The effect of achievement motivation on job satisfaction. indicated by the coefficient of determination R2 (R square) = 0.461% and the remaining 53.9% is determined by other factors. The results of simple regression analysis show the regression equation Ŷ = 8.638+ 0.290X2, which means an increase in value of 0.290. The results of simple regression analysis show the regression equation Ŷ= 8.638+0.309X3 which means that an increase of 0.309 There is a positive and significant influence of instructional leadership (X1), achievement motivation (X2), and quality of work life (X3) together on job satisfaction. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = which means that Job Satisfaction jointly influences teacher performance by 63.0% and the remaining 37.0% is determined by other factors. The results of simple regression analysis show the equation Ŷ =8.638+ 0.838X1 + 0.290X2+0.309X3. Keywords: Instructional Leadership, Achievement Motivation, Quality of work life, Job Satisfaction